Current state of preliminary process of high speed railway lines in the Czech republic - Pinkava, Marek (University of Pardubice, 2018)
The article is focused on current state of preliminary process of so called “Rapid Services” in the Czech Republic. The concept of “Rapid Services” and approach to high speed railway in the Czech Republic are characterized in a brief way. Current state of preliminary process as well as proposed following steps are mentioned.
Keywords: high-speed railway; high-speed line; preliminary process of construction works